The Influence of Social Media Marketing on the Decision to Use Grab Online Transportation Services among Students - Gultom, Miranda; Manalu, Darma; Simangunsong, Ridhon. MB. (Manunggal Halim Jaya, 2024)
This study aims to determine the effect of social media marketing on decisions to use Grab online transportation services for students of Universitas HKBP Nommensen Medan. The type of research used in this research is a quantitative approach. The population in this study were all students of Universitas HKBP Nommensen Medan who had used grab online transportation services whose population size was unknown. Based on the Lemeshow formula, the sample used in this study was 96 respondents who were taken randomly to represent each faculty. The results showed that Social Media Marketing significantly influences service usage decisions, this is shown in the partial test results (t test) t-value 8.632> t-table 0.2006 and a significance value of 0.000 <0.05. The Coefficient of Determination (R2) is obtained at 0.442, meaning that the Service Usage Decision variable can be explained by the Social Media Marketing variable by 44.2% and the remaining 55.8% is influenced by other variables outside of this research variable, such as Service Quality, Price, and so on. The conclusion in this study is that Social Media Marketing has a positive and significant effect on the Decision to Use Grab Online Transportation Services for Students of Universitas HKBP Nommensen Medan.